Long‐term photometry of three active red giants in close binary systems: V2253 Oph, IT Com and IS Vir. Issue 7 (1st August 2013) - Oláh, K.; Moór, A.; Strassmeier, K.G.; Borkovits, T.; Granzer, T.
Abstract We present and analyze long‐term optical photometric measurements of the three active stars V2253 Oph, IT Com and IS Vir. All three systems are single‐lined spectroscopic binaries with an early K giant as primary component but in different stages of orbital‐rotational synchronization. Our photometry is supplemented by 2MASS and WISE near‐IR and mid‐IR magnitudes and then used to obtain more accurate effective temperatures and extinctions. For V2253 Oph and IT Com, we found their spectral energy distributions consistent with pure photospheric emission. For IS Vir, we detect a marginal mid‐IR excess which hints towards a dust disk. The orbital and rotational planes of IT Com appear tobe coplanar, contrary to previous findings in the literature. We apply a multiple frequency analysis technique to determine photometric periods, and possibly changes of periods, ranging from days to decades. New rotational periods of 21.55±0.03 d, 65.1±0.3 d, and 23.50±0.04 d were determined for V2253 Oph, IT Com, and IS Vir, respectively. Splitting of these periods led to tentative detections of differential surface rotations of δP/P ≈ 0.02 for V2253 Oph and 0.07 for IT Com. Using a time‐frequency technique based on short‐term Fourier transforms we present evidence of cyclic light variations of length ≈ 10 yr for V2253 Oph and 5‐6 yr for IS Vir. A single flip‐flop event has been observed for IT Com of duration 2–3 yr. Its exchange of the dominant active longitude had happened close to a time of periastron passage, suggesting some response of the magnetic activity from the orbital dynamics. The 21.55‐d rotational modulation of V2253 Oph showed phase coherence also with the orbital period, which is 15 times longer than the rotational period, thus also indicating a tidal feedback with the stellar magnetic activity. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)